APPLICATION OF ISLAMIC BUSINESS ETHICS IN PRODUCTION FOR MSMEs AT UINFAS BENGKULU CANTEEN - Puspita, Yeza; Yusril, Yusril; Asnaini, Asnaini (Jurnal Asy-Syukriyyah, 2024)
This research analyzes the application of Islamic business ethics in production at Micro, Small and Medium Enterprises (MSMEs) in the canteen of Fatmawati Sukarno State Islamic University (UINFAS) Bengkulu. The aim of this research is to explore how the principles of Islamic business ethics are applied in production practices as well as the challenges faced by MSMEs in the campus environment. The method used is qualitative research with a descriptive approach, involving interviews and direct observation. The research results show that the UINFAS canteen has implemented the five principles of Islamic business ethics: the Principles of Tauhid, Honesty, Justice, Free Will, and Responsibility. Although the application of this ethic has a positive impact on the reputation and competitiveness of MSMEs, there are challenges such as employee awareness and limited resources. It is hoped that this research will provide insight for business actors about the importance of ethics in business and its contribution to the welfare of society.